Value chain innovations for technology transfer in developing and emerging economies: Concept, typology and policy implications - Johan F. M. Swinnen; Rob Kuijpers (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2016)
The adoption of modern technologies in agriculture is crucial for improving productivity of poor farmers and poverty reduction. However, the adoption of modern technology has been disappointing. The role of value chains in technology adoption has been largely ignored so far, despite the dramatic transformation and spread of modern agri-food value chains. We argue that value chain organization and innovations can have an important impact on modern technology adoption, not just by downstream companies, but also by farmers. We provide a conceptual framework and an empirical typology of institutional innovations through which value chains can contribute to technology transfer to agriculture in developing and emerging countries.
Keywords: 330; Technologietransfer; Agrartechnik; Betriebliche Wertschöpfung; Innovationsakzeptanz; Agroindustrie; Entwicklungsländer; Schwellenländer